Are adaptable employees more likely to stay? Boundaryless careers and career ecosystem perspectives on career adaptability and turnover. Issue 4 (21st November 2021) - Wang, Fuxi; Xu, Ying; Zhou, Xinyi; Fu, Anguo; Guan, Yanjun; She, Zhuolin; Wang, Zhimei; Bi, Yanzhao
Abstract: Employees with higher career adaptability (CA) have been shown in previous research to be more likely to build high‐quality social exchange relations with current employers, thereby displaying a lower intention to leave. Based on boundaryless careers and career ecosystem perspectives, this study aimed to challenge and enrich the extant understanding of this important question by examining the mixed effects of CA on turnover behavior. Results from a three‐wave survey study with 179 Chinese employees show that after controlling the baseline turnover intention (Time 1), CA (Time 1) predicted both affective commitment and relative deprivation at Time 2 (6 months after Time 1), which in turn produced opposite effects on voluntary turnover behavior at Time 3 (12 months after Time 1). Moreover, the boundaryless career mindset positively moderated the relationship between CA and relative deprivation and strengthened the indirect positive effect of CA on turnover behavior via relative deprivation. These results offer a more comprehensive and balanced view of the mixed role of CA in employees' turnover behavior and carry important implications for human resource management.